Analisis Tingkat Kesehatan Bank Untuk Mengukur Kinerja Keuangan Pada Bank Umum Syariah Di Indonesia Periode 2012-2014 - Margono, Margono; , Zulfa Irawati., SE., MSi (2016)
This study aims to determine the level of financial performance of Islamic Banks in the value using the Capital, Assets, Management, Earnings and, Liquidity (CAMEL). The population in this study using Islamic Banks in Indonesia 2012-2014. The study sample as many as eight Islamic Banks, which use a sampling method used is purposive sampling. Data analysis methods used by the CAMEL method using the ratio of Capital Adequacy Ratio (CAR), Assets Quality (KAP), Allowance for Assets (PPAP), Net Profit Margin (NPM), Return on Assets (ROA), Operating Expenses Against Operating income (ROA), Cash Ratio (CR) and a loan to deposit ratio (LDR). Overall results of the financial performance of Islamic Banks with CAMEL method that indicates a healthy predicate is CAR, KAP, PPAP, ROA, ROA, and LDR CR. But in the aspect ratio management by NPM predicate unhealthy. Islamic Banks suggested increase in net income and operating income to that aspect of management by using the ratio of net profit margin in a healthy state.